REVITALISASI WARISAN NILAI BUDAYA BUTON DALAM FILOSOFI SARA PATAANGUNA (ADAT YANG EMPAT) SEBAGAI WUJUD KEARIFAN LOKAL - La Ode Dirman (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2016)
The legacy of value is not automatically embedded in the minds of every individual but through the process. Individuals since childhood instill the feelings, desires, passions, and emotions that are needed throughout his life. Through the process of learning about patterns of action in relationships with all kinds of individuals who have a variety of positions and roles. In this process, a person will learn all kinds of norms, rules that exist in the customs that live in the community which then becomes a steady pattern. Similarly, the ideology of the customary norms of the sultanate of Buton inherited from the generation of generation up to now, but also in its development under threat of inheritance. Meanwhile, the customary norm of Buton called sara pataanguna contains the value of local wisdom is needed to maintain its existence in every individual activity. Therefore, it is necessary to revitalize constructive cultural values which in this reform era is very useful for the interests of development both for individual self as well as the collectivity of its supporting community especially in the field of social, cultural, political and economic development. Keywords : revitalization, ideology, norm, stereotipe , local wisdom